Altamira 2042: Feminist performance and the Anthropocene (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This essay deals with climate crisis through the discussion of Altamira 2042, a multimedia performance-installation by Gabriela Carneiro da Cunha, which addresses the social, cultural and environmental consequences of the construction of the Belo Monte hydroelectric plant, responsible for one of the worst ecocides of the 21st century. Belo Monte’s dystopia highlights the conflict between the interests of global capital, the forces of “progress," and the survival of the local population and their social organizations, knowledge and traditions; between modernity's instrumental technology and their ancient technologies. The essay focuses on how feminist performances can respond to the specter of mass extinction and climate change.